Knowledge, Technology and Economic Growth Recent Evidence from OECD Countries - Bassanini, Andrea (OECD Economics Department Working Papers, 2000)
In this paper we present an international comparison of growth trends in the OECD countries, with a special attention to developments in labour productivity - allowing for human capital accumulation - and multifactor productivity (MFP) - allowing for changes in the composition of fixed capital. An attempt is also made to identify both the embodied (in particular in ICT equipment) and disembodied components of technical progress. The possible relation between improvements in MFP and the accumulation of knowledge (as proxied by R&D expenditures) is discussed, and some tentative policy considerations are advanced, mainly with reference to general framework conditions that might have a bearing in fostering technological changes. The main conclusions are that some "traditional" factors lay behind the disparities in growth patterns across the OECD countries. In particular, they refer to the ability of countries to employ their labour force. There also seem to be some new factors behind ...